HUBUNGAN STRES DAN DUKUNGAN KELUARGA DENGAN RISIKO KEJADIAN INSOMNIA PADA MAHASISWA FIKES UPNVJ DI ERA PANDEMI COVID-19 - Raniah Salma, (2021)
Insomnia is a sleep disorder problem caused by many factors. The stress felt by students during the Covid-19 pandemic was due to the implementation of Distance Learning (PJJ) which added to the burden of lectures. Family support is one of the supporting factors during the pandemic. The purpose of this study was to determine the relationship between stress and family support with the risk of insomnia among students of the Faculty of Health Sciences UPN Veteran Jakarta in the Covid-19 pandemic era. This study used a cross-sectional study design. The sampling technique used is proportionate stratified random sampling and purposive sampling with a total sample of 355 respondents. The research data was collected using a questionnaire distributed online via google form. The research instruments used were DASS-21, PSS-Fa, and ISI. The data analysis of this research is univariate analysis and bivariate analysis using chi square test. The results showed that there was a relationship between stress and insomnia (p = 0.000) with an POR value of 6.5 (95% CI: 3.8-10.8). Therefore, students should be able to find things to manage stress so that stress can be controlled and does not get worse.